The Effect of Mutation at Thr 295 of Saccharomyces cerevisiae eRF1 on Suppression of Nonsense Codons and eRF1 Structure - PRIMA ENDANG SUSILOWATI; PINGKAN ADITIAWATI; FIDA MADAYANTI; . AKHMALOKA (Indonesian Society for microbiology, 2008)
The termination of translation in Saccharomyces cerevisiae is controlled by two interacting polypeptide chain release factors, eRF1, and eRF3. Two regions in eRF1, at position 281-305 and 411-415, were proposed to be involved on the interaction to eRF3. In this study we have constructed and characterized eRF1 mutants at position 295 from threonine to alanine and serine residues resulting in eRF1(T295A) and eRF1(T295S) respectively. The mutations did not affect the viability or temperature sensitivity of the cells. The stop codons readthrough of the mutants were analyzed in vivo using PGK-stop codon-LACZ gene fusion and the results showed that thesuppression of the mutants was increased in all of the codon terminations. The suppression of the UAG codon was the high for both mutants, with a 7-fold increased for eRF1(T295A) and a 9 fold increase for eRF1(T295S). The suppressor activity of eRF1(T295S) was higher compared to that of eRF1(T295A), suggesting that the accuracy of translational termination in eRF1(T295S) was lower than that of eRF1(T295A). Computer modeling analysis using Swiss-Prot and Amber version 9.0 programs revealed that the overall structure of eRF1 mutants has no significant difference with the wild type. However, substitution of threonine to serine on eRF1(T295S) triggered a secondary structure change on the other motif of the C-terminal domain of eRF1. This observation did not occur for on eRF1(T295A). This suggests that the high stop codon suppression on eRF1(T295S) is probably due to the slight modification of the structure of the C terminal motif.